Pattern of Viteoretinal Diseases in Patients of Kangra Valley - Aditi Parashar; Rajeev Tuli; Rattan K. Sharma; Mukta Sharma Shalu Gupta (Delhi Journal of Ophthalmology)
Background: This study may be the foundation pillar for future planning and need for set up of vitreoretinal care services in Dr. Rajendra Prasad Government Medical College, Kangra at Tanda, India. Aims and Objectives: To determine the pattern of vitreoretinal diseases in patients attending the retina clinic of Dr. Rajendra Prasad Government Medical College, Kangra, Tanda, India. Materials and Methods : A retrospective analysis of the patients attending the retina clinic over a period of one year 2015 to 2016 was carried out from the out patient register. The patients with a very hazy media and posterior uveitis were excluded from the study. Statistical Analysis: The significance was determined using percentage. Results : In our study out of 424 cases, 237 (55.96%) were males and 187 (44.10%) were females. In our first age group less than equal to 40 years, out of 122 patients there were 72 males (59.01%) and 50 (40.98%) females and diabetic retinopathy was the commonest disorder in them followed by retinal detachment. In the second age group more than 40 years there were 302 patients including, 165 (54.63%) males and 137 (45.36%) females. Age related macular degeneration (ARMD) was the commonest disorder in them followed by diabetic retinopathy. Conclusion: With increase in age there in increase in number of retinal disorders. Out of the total diseases Diabetic retinopathy was the commonest retinal disorder (27.59%) and there was a male preponderance to it. The second most common retinal disorder was ARMD (20.04%), followed by retinal detachment (11.55%).